BACKGROUND RADIATION LEVELS NEAR A MINERAL SAND MINING FACTORY IN SRI LANKA: CORRELATION OF RADIATION MEASUREMENTS WITH MICRONUCLEI FREQUENCY. Issue 1 (24th February 2020) - Warnakulasuriya, Tania; Williams, Senani; Weerakkody, Thiwanka; Dabarera, Mangala; Rodrigo, Kusum; Waduge, Vajira Ariyaratna; Ediriweera, Dileepa; Siriwardena, Niroshan; Wickremasinghe, Rajitha
Abstract: Lanka Mineral Sands Ltd (LMS) is a company operating in Pulmoddai, Sri Lanka, mining for rare earth minerals along with monazite which contains thorium that emits ionizing gamma and alpha radiation on decay. The objective of the study was to determine the background radiation levels and selected radionuclides and then to correlate these levels with the frequency of micronuclei (MN) among persons residing in the vicinity of LMS. A cross-sectional study was conducted among persons of both sexes between 35 and 45 years of age residing in the vicinity of LMS. Background radiation measurements were obtained by a survey metre, and gamma spectrometry was done on soil samples. Five millilitres of venous blood was drawn for cytokinesis-blocked MN assay. Background radiation levels measured by the survey metre; 232 Th, 226 Ra and 210 Pb mass activities in soil were highest in the samples collected from the LMS. The background radiation measurements positively correlated with MN frequency although the magnitude of the correlation was small ( r  = 0.176, p  = 0.04). This implies that chronic long-term exposure to low-dose radiation may result in genotoxicity. Prospective large-scale studies are recommended to evaluate the long-term effect of exposure to low-dose radiation at Pulmoddai.